Overview of compressed air energy storage projects and regulatory framework for energy storage - Matos, Catarina R. (2022)
Energy storage (ES) plays a key role in the energy transition to low-carbon economies due to the rising use of intermittent renewable energy in electrical grids. Among the different ES technologies, compressed air energy storage (CAES) can store tens to hundreds of MW of power capacity for long-term applications and utility-scale. The increasing need for large-scale ES has led to the rising interest and development of CAES projects. This paper presents a review of CAES facilities and projects worldwide and an overview of the ES regulatory framework and policies. It performs two benchmarking procedures: first, a benchmark of CAES worldwide, and second a benchmark of ES regulatory frameworks, policies, drivers and barriers. It tries to understand whether the development or cancellation of CAES projects globally is in any way related to the development of ES policies. This study addresses policy perspectives and specific ES regulatory framework recommendations, contributing to public policy design in the attempt to overcome the regulatory barriers to the ES sector and influencing the deployment of ES and, specifically, CAES. Removing current regulatory barriers and establishing new and broader policies are essential to provide ES and CAES technologies with the right opportunities to develop, enhance efficiency, increase operational experience, and reduce costs.